Cak Nur on Politics: Indonesian Political Islam and the Role of Islamic Politics - Hamudy, Nurul Annisa; Hamudy, Moh Ilham A (Al-Risalah, 2020)
The Indonesian political elites tend to use Muslims for their personal interests, instead of making Islam as their moral guide in the political arena, despite Nurcholish Madjid’s (Cak Nur) secularization is needed. For this reason, this research discusses the political ideals of Cak Nur, especially the idea of ​​secularization in the midst of the current political Islam in Indonesia. Using a descriptive method, literature study, and a qualitative approach, the results of the study showed that Islam essentially is not merely a formal structure or composition and collection of laws of the state and government. Islam is the embodiment of tawḥīd. It is a spiritual force that can give birth to a soul that is ḥanīf, inclusive, democratic, and respects society’s pluralism. Therefore, an understanding of more advanced Islamic teachings, such as Cak Nur’s secularization concept which according to Cak Nur's does not lead to secularism; as well as the need for freedom of thought, an idea of ​​progress, and openness to ideas are a necessity in Indonesia. As such Moslem should use a secular lens to view worldly matters that need rational and objective thinking, rather than using faith, Islamic law, ʻaqīda (creed), and ʻibāda (worship) which are spiritual matters.